Comparative Study of the General Election Commission (KPU) in the United States and South Korea - Sinta Alfi Rosyida; Basuki Kurniawan (Rechtenstudent, 2023)
According to Article 22 E of the 1945 Constitution of the Republic of Indonesia, Indonesia is a democratic country where the people hold the highest power with a representative system, namely general elections. General elections are one way for people to participate in politics. The type of research used is library research, where the research is centered in the library to obtain data without carrying out field research. So the data source is obtained using literature or regulations and norms related to the problem to be studied, namely in the form of books that examine the Position and Authority of the General Election Commission (KPU). The results of the research are 1) That the Juridical Study of the Position and Authority of the General Election Commission (KPU) in the perspective of the State Administration of the Republic of Indonesia is to realize the instrument of popular sovereignty, which aims to create a legitimate government and provide a way for the people to express their ambitions and interests. 2) That the comparison of the position and authority of the General Election Commission (KPU) in the United States and South Korea is that the United States has two general election commissions, namely the Electoral College and the Federal Election Commission (FEC).